"Personally, It Does Not Bother Me All that Much": Nuclear Risk Assessments and Strategic Choice among Stakeholders in Post-Fukushima France. Issue 4 (2nd October 2021) - Schweitzer, Julie; Mix, Tamara L.
ABSTRACT: Nuclear technology is often associated with risk, a connotation amplified by major nuclear disasters including Japan's 2011 Fukushima Daiichi power plant catastrophe. Assessments of risk associated with nuclear energy are complex, reflecting political and economic interests in the technology. Countries like France that rely heavily on nuclear power make efforts to craft messages about nuclear risk to both normalize and prevent resistance to the technology. Normative, oppositional, and monitoring stakeholders compete to define the meaning of nuclear energy in France. As actors discuss the future of the industry, they integrate the concept of risk into daily narratives. Employing data from 27 semi-structured interviews with 28 key stakeholders, our study considers France's unique relationship with nuclear energy to address risk and tactical choice in a context that normalizes a contested technology. Our analysis highlights the dominant position of normative stakeholders in influencing nuclear risk perceptions and weakening oppositional tactical choices.